Vector competence of Aedes bromeliae and Aedes vitattus mosquito populations from Kenya for chikungunya virus - Mulwa, Francis (PLoS Negl Trop Dis, 2018)
BACKGROUND: Kenya has experienced outbreaks of chikungunya in the past years with the most recent outbreak occurring in Mandera in the northern region in May 2016 and in Mombasa in the coastal region from November 2017 to February 2018. Despite the outbreaks in Kenya, studies on vector competence have only been conducted on Aedes aegypti. However, the role played by other mosquito species in transmission and maintenance of the virus in endemic areas remains unclear. This study sought to determine the possible role of rural Aedes bromeliae and Aedes vittatus in the transmission of chikungunya virus, focusing on Kilifi and West Pokot regions of Kenya. METHODS: Four day old female mosquitoes were orally fed on chikungunya virus-infected blood at a dilution of 1:1 of the viral isolate and blood (10(6.4) plaque-forming units [PFU]/ml) using artificial membrane feeder (Hemotek system) for 45 minutes. The engorged mosquitoes were picked and incubated at 29–30°C ambient temperature and 70–80% humidity in the insectary. At days 5, 7 and 10 post-infection, the mosquitoes were carefully dissected to separate the legs and wings from the body and their proboscis individually inserted in the capillary tube containing minimum essential media (MEM) to collect salivary expectorate. The resultant homogenates and the salivary expectorates were tested by plaque assay to determine virus infection, dissemination and transmission potential of the mosquitoes. RESULTS: A total of 515 female mosquitoes (311 Ae. bromeliae and 204 Ae. vittatus) were exposed to the East/Central/South Africa (ECSA) lineage of chikungunya virus. Aedes vittatus showed high susceptibility to the virus ranging between 75–90% and moderate dissemination and transmission rates ranging from 35–50%. Aedes bromeliae had moderate susceptibility ranging between 26–40% with moderate dissemination and transmission rates ranging from 27–55%. CONCLUSION: This study demonstrates that both Ae. vittatus and Ae. bromeliae populations from West Pokot and Kilifi counties in Kenya are competent vectors of chikungunya virus. Based on these results, the two areas are at risk of virus transmission in the event of an outbreak. This study underscores the need to institute vector competence studies for populations of potential vector species as a means of evaluating risk of transmission of the emerging and re-emerging arboviruses in diverse regions of Kenya.